Penciptaan Informasi Keruangan Waktu Musim Hujan dan Kemarau untuk Mengantisipasi Bencana Banjir dan Kekeringan - Purwaamijaya, Iskandar Muda (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
AbstractThe purpose of the study (1) design a conceptual model of spatial information during the rainy season and dry season to anticipate floods and drought, (2) create a functional model of the results of modeling conceptual, (3) implements spatial information during the rainy season and dry season to anticipate floods and droughts, Method of solving the problem is with descriptive and analytical techniques used spatial analysis and matrix. The conclusion of the study (1) the conceptual model results matrix analysis concluded basic map that used to be a small-scale (scope of West Java province) and refers to the raw information used by BPLHDs (Environmental Management Agency Region), (2) the functional model results matrix analysis concludes the number of components of spatial information to be presented is the 8 components of spatial information point (point), four components of spatial information line (line), 8 components of spatial information area (polygon) and 12 components of spatial information text (annotation), (3) implementation of the model results matrix analysis produces unity polygon graphics information to the boundary of the village, sub-district boundaries, county boundaries, the provincial boundaries, bodies of water catchment areas, wind roses, land use stored in the record and file levels. Unity of graphic information point for the station rainfall and bodies of water that is stored in the record and file levels. Unitary information line for a body of water, Isohyets, isobars and isotemp stored in the record and file levels.